Hormone replacement therapy perspectives - Kissinger, Dohn (Frontiers in Global Women's Health, 2024)
Hormone replacement therapy (HRT), also known as menopausal hormone therapy (MHT), was looked upon as a fountain of youth that kept women young and reduced cardiovascular disease. This led to a large-scale study called the Women's Health Initiative (WHI) that was conducted to show the cardiovascular benefits of HRT. This study was suspended early because of adverse side effects. The USFDA responded by slapping a “black box” warning on all HRT products. USFDA-approved bioidentical HRT formulations are safe and effective. We propose that these formulations have the “black box” warning removed so that doctors feel more confident in prescribing these products for symptoms of menopause and chronic conditions such as cardiovascular health. We propose eliminating the sale of products containing medroxyprogesterone acetate (MPA) because of the increased risk of heart attacks and breast cancers associated with this medication.